NOVEL APP FOR PRACTICAL DOSING OF COMBINATION ANTIRETROVIRAL THERAPY IN PEDIATRIC PATIENTS WITH HIV/AIDS. Issue 1 (14th December 2015) - Anker, J.N.Y. van den; Sanduja, S.; Ferrer, Kathleen; Rakhmanina, N.; Pfister, Marc
Abstract : Background: Combination antiretroviral therapy (ART) of HIV infection in pediatric patients requires lifetime daily administration of a minimum of three antiretroviral drugs (ARVs). A wide range of dosing regimens is used in these patients. Dosing errors are common and may result in ARVs overdosing with associated toxicities orARVs underdosing resulting in the development of viral resistance. Attempts have been made to produce compact ARVs dosing charts, but have not been successful due to the complexity of regimens, ARV drug-drug interactions and compatibility restrictions. Advances in mobile technology have brought new opportunities for creating dosing support tools, including smartphone applications (Apps). In middle and low income countries, most affected by HIV epidemic, smartphones and tablets are widespread among medicalprofessionals. A mobile Appthat produces correct pediatric ARVs dosing, warnings for compatibility and most important drug interactions, has the potential to significantly improve the quality of ART in HIV-infected children. Methods: Using reference ARVs guidelines from the 2014 Guidelines for the Use of Antiretroviral Agents in Pediatric HIV Infection by the HHS Panel on Antiretroviral Therapy and Medical Management of HIV-Infected Children and 2013 World Health Organization pediatric HIV treatment guidelines we have developed a novel drug prescription App for pediatric ART. Results: A noveldrug prescription App, based on up to date references, permits health care providers to easily access up-to-date dosing information and quickly calculate individualdoses of all ARVsbased on a patient's characteristics (e.g. weight, height, age, serum creatinine value). Most importantly, the App can be easily updated and synchronized remotely, allowing for timelydelivery of most important pediatric ARVs dosing updates. Conclusion: The smartphone App for pediatric ARVs can serve as an important healthcare worker support tool in the treatment of HIV-infected infants and children. Pharmacometric modelingcan be built in such App to leverage resistance and clinical patient data, individualize dosing strategies particularly for co-morbidities and optimize ART outcome. Most importantly, in the era of the global scale up of pediatric ART and task shifting of ART management to nursing staff, this App can have significant capacitating effect on the healthcare workforce.